Strategies for English Directives Applied by Indonesian Students to Obtain Information from Chatbot - I Gusti Ngurah Adi Rajistha; Dewa Ayu Kadek Claria (Center of Language and Cultural Studies [CLCS], 2023)
Politeness in language can be seen from a socio-cultural and linguistic point of view. From the point of view of language, politeness can be seen from the linguistic structure and the meaning conveyed. Using polite language is not only between individuals who are part of society but it is also with chatbots, which is used to increase knowledge about politeness in language. This study examines politeness strategies used by students in delivering directives. ELIA (English Literature Information Assistant) is a chatbot created based on FAQs from students, and ELIA is used to provide information about lectures, final assignments, and other information related to study programs. The research method that was applied in this study is a qualitative descriptive method obtained from the ELIA admin and questionnaires. Data were collected after the ELIA is upgraded to be able to record the communication between students and ELIA. The data collected were in the form of textual communication records. The findings from the study indicate that the strategies applied by students to obtain information are directive strategies, namely direct strategies (40.2%), on-record indirect strategies (14.8%), off-record indirect requests (19%), and nonsentential strategies (26%). Based on the directive strategy used, direct and nonsentential strategies are strategies that do not show politeness. Strategies that show politeness are on-record indirect strategies and off-record indirect requests. In other words, the politeness strategy in directives applied by students is 33.8% of the total requests used.